Advanced strategy of grid-forming wind storage systems for cooperative DC power support - Zhang, Xiaoke; Wang, Jiaqi; Gao, Zan; Zhang, Shaofeng; Teng, Weijun (Frontiers in Energy Research, 2024)
Grid-forming (GFM) wind storage systems (WSSs) possess the capability of actively building frequency and phase, enabling faster frequency response. The frequency regulation power of GFM WSSs is provided by both the rotor of wind turbine and the battery storage (BS) in parallel with DC capacitor. However, with existing control strategies, the energy storage immediately responds to both small and large grid disturbances. The frequent responses significantly decrease the lifespan of energy storage. To address this issue, a cooperative strategy between rotor and energy storage is necessary. This paper proposes an advanced strategy of GFM WSSs for cooperative DC power support. The cooperative principle is that for small disturbances, the BS is disabled and total frequency regulation power is provided by the rotor, while for large disturbances, the BS is enabled to cooperatively provide power support with the rotor. The proposed cooperative strategy can decrease the charging and discharging times of BS with a small range of rotor speed fluctuation, and then the service life of BS can be significantly extended. Simulation results validate the effectiveness and superiority of the proposed strategy.